The impact of writing practices on enhancing productive skills among pre-intermediate EFL learners - Namaziandost, Ehsan; Esfahani, Fariba Rahimi (Penerbit Universiti Kebangsaan Malaysia, 2018)
Writing and speaking are the productive skills of a language which share similar elements. However, there has been rare endeavor to examine the effect of writing practice on both speaking and writing improvement of the learners.Therefore, in this study we tried to check the impact of writing practice on the productive skills among pre-intermediate EFL learners. To do this study, 50 Iranian pre-intermediate EFL learners were selected among 75 students at a private English Language Institute. Then, the selected participants were divided into two groups; one experimental (n=25) and one control group (n=25). After that, a test consisted of both speaking and writing was administered as pretest. Then, the experimental group received the treatment which was learning productive skills through excessive writing practices. The control group did not receive any treatment and they were taught in the classroom using traditional methods of teaching. The treatment took eleven sessions of 60 minutes each under the guidance of the supervisor. After the treatment, both groups took the post-test of speaking and writing. Data were analyzed by one-way ANCOVA. The results indicated that not only writing proficiency, but also the speaking proficiency of the experimental group had significantly improved. The findings revealed that the experimental group significantly outperformed the control group (p < .05) on the post-test. Finally, implications arising from the findings and suggestions for further research were explained.